Photoelectrocatalytic material electrode, preparation method and application

By combining the titanium oxide-doped cellulose nanofiber hydrogel with MIL-100 (Fe) nanoparticles, a two-three-dimensional structure photoelectrocatalytic material electrode is formed, which solves the problem of low reaction rate of photoelectrodes on tetracycline antibiotics and catalyst loss, and achieves efficient tetracycline degradation and material stability.

CN119660898AActive Publication Date: 2025-03-21HUAIHUA HYUNDAI KANGHENG ENVIRONMENTAL PROTECTION ENERGY CO LTD

Patent Information

Application Number
CN202411911228.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-21
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

The reaction rate of existing photoelectrodes to tetracycline antibiotics is low, and titanium oxide powder and MOFs powder are prone to loss, resulting in difficulty in recycling and secondary contamination.

Method used

A cellulose nanofiber hydrogel doped with titanium oxide is used as the electrode substrate, and MIL-100 (Fe) nanoparticles are uniformly loaded thereon to form a double three-dimensional structured photoelectrocatalytic material electrode.

Benefits of technology

The reaction rate and stability of photoelectrocatalytic materials are improved, the loss of catalyst is reduced, and the efficient degradation of tetracycline is achieved, and excellent catalytic effect is shown under visible light conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119660898A_ABST
    Figure CN119660898A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of photoelectrocatalysis materials, in particular to a photoelectrocatalysis material electrode, a preparation method and application. The electrode is prepared by the method. The method comprises the following steps: preparing cellulose nanofiber hydrogel doped with titanium black; after the cellulose nanofiber hydrogel doped with the titanium black is subjected to first pretreatment, titanium strips subjected to second pretreatment are respectively pasted on the front surface and the back surface of one end of the cellulose nanofiber hydrogel doped with the titanium black to obtain a cellulose nanofiber hydrogel electrode plate doped with the titanium black; the part, located below the titanium strip, of the electrode plate is immersed in an MOFs dispersion solution, loading treatment is conducted under stirring, and the double-three-dimensional-structure photoelectrocatalysis material electrode is obtained. The application refers to application of the electrode in degradation of tetracycline wastewater. The problems that an existing photoelectrode is low in reaction rate for tetracycline antibiotics and titanium black powder and MOFs powder are prone to loss can be solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photoelectrocatalytic materials, and in particular to a photoelectrocatalytic material electrode, a preparation method and an application thereof. Background Art

[0002] Tetracycline antibiotics are one of the most widely used antibiotics due to their low price, high applicability and excellent bactericidal and antibacterial effects. Since wastewater containing tetracycline is discharged directly into the environment without treatment, it will damage the aquatic ecosystem and affect the survival and reproduction of aquatic organisms. In addition, the presence of tetracycline residues and tetracycline resistance genes may pose a potential threat to human health. By treating tetracycline wastewater, we can reduce the exposure of tetracycline to the human body and reduce the risk of the spread of tetracycline resistance, thereby protecting public health.

[0003] In recent years, photoelectrocatalytic technology has been gradually used for the degradation of organic pollutants, which has obvious advantages in terms of recyclability and reproducibility. However, the treatment efficiency of photoelectrodes for tetracycline antibiotics often shows a low reaction rate due to the limited active area of ​​the electrode and its mutual restriction with the height of the treatment liquid. In addition, the photoresponse characteristics, stability and charge separation efficiency of the photoelectrode in the photoelectrocatalytic process are all important factors affecting the efficiency of photoelectrocatalysis. Therefore, the selection of electrode substrates, catalysts and performance optimization are crucial to the implementation of photoelectrocatalytic technology.

[0004] Titanium-based compounds are one of the most promising electrode materials in the field of photoelectrocatalysis. Magneli phase titanium oxide (Ti4O7) has attracted the attention of researchers due to its small bandgap, good visible light response and high stability. However, the original titanium oxide has a low charge separation rate and limited ability to degrade pollutants. It needs to be doped with elements or modified with single atoms / compounds to increase the charge separation efficiency of the titanium oxide electrode. MOFs have large specific surface area, abundant active sites, adjustable band gap structure and unique three-dimensional structural characteristics, that is, they have metal clusters and organic ligands, and show the ability to absorb ultraviolet or visible light. This light absorption process stimulates the generation of photogenerated electron-hole pairs, and the photogenerated electrons / holes can be effectively separated in space under suitable conditions, showing the potential of MOFs as photocatalysts or photoelectric materials. Compared with other MOFs, Fe-based MOFs have broad application prospects in the field of photoelectrocatalysis due to their higher physicochemical stability, thermal stability and water stability, and the fact that Fe(III) oxide is more easily excited by visible light irradiation, and Fe is one of the most abundant metal elements in the earth's crust.

[0005] However, titanium dioxide powder and MOFs powder are easy to lose, making recycling difficult and easily causing secondary pollution. Therefore, it is urgent to find an environmentally friendly, stable and structurally excellent electrode substrate to expand the application of titanium dioxide and MOFs in the field of photoelectrocatalytic degradation of organic pollutants.

[0006] In summary, it is necessary to provide a photoelectrocatalytic material electrode, a preparation method and an application to solve the problem of low reaction rate of existing photoelectrodes to tetracycline antibiotics and the problem of easy loss of titanium dioxide powder and MOFs powder. Summary of the invention

[0007] The present invention aims to provide a photoelectrocatalytic material electrode, a preparation method and an application thereof. The specific technical scheme is as follows:

[0008] In a first aspect, the present invention provides a method for preparing a photoelectrocatalytic material electrode, comprising:

[0009] Step S1, preparing titania-doped cellulose nanofiber hydrogel;

[0010] Step S2, after the titania-doped cellulose nanofiber hydrogel has been subjected to the first pretreatment, titanium bars subjected to the second pretreatment are respectively attached to the front and back sides of one end of the titania-doped cellulose nanofiber hydrogel to obtain a titania-doped cellulose nanofiber hydrogel electrode sheet;

[0011] Step S3, immersing the portion of the electrode sheet below the titanium strip into a MOFs dispersion solution, and performing a loading treatment under stirring to obtain a dual three-dimensional structure photoelectrocatalytic material electrode.

[0012] Optionally, in step S1:

[0013] First, a hydrogel solution A is prepared. Specifically, 20 to 40 g of cellulose nanofiber hydrogel, 0.3 to 0.6 g of agar powder and 16 to 32 mL of deionized water are mixed, and then the mixture is subjected to a water bath treatment and a first continuous stirring treatment to obtain a hydrogel solution A.

[0014] Secondly, under the water bath treatment and the first stirring treatment, 0.25-0.35 g of titanium dioxide powder is added to the hydrogel solution A and mixed;

[0015] Then, the mixture was stirred for a second time at room temperature until it was completely dissolved, thereby obtaining solution B;

[0016] Finally, the solution B is poured into a culture dish, and an acidifier and a cross-linking agent are added thereto. After drying, the titanium dioxide-doped cellulose nanofiber hydrogel is obtained.

[0017] Optionally, the temperature used in the water bath treatment is 85-90°C; the rotation speed used in the first stirring treatment is 400-500rpm, and the stirring time is 3-5min; the rotation speed used in the second stirring treatment is 1000-1100rpm, and the stirring time is 2-3h.

[0018] Optionally, the acidulant comprises sulfuric acid; the concentration of the acidulant is 0.5-2.0 mol / L, and the volume is 3-4 mL; the crosslinking agent comprises N,N′-methylenebisacrylamide solution; the mass concentration of the N,N′-methylenebisacrylamide solution is 3.5-4.5wt%, and the volume is 3-4 mL; the drying temperature adopted in the drying treatment is 50-80°C, and the drying time is 45-60 min.

[0019] Optionally, the first pretreatment includes sequentially performing deionized water cleaning and cutting on the titania-doped cellulose nanofiber hydrogel; the second pretreatment includes first ultrasonically removing impurities from the surface of the titanium sheet and then cutting it into titanium strips; the adhesive includes an ethanol solution of polyvinyl pyrrolidone.

[0020] Optionally, the MOFs dispersed solution comprises dispersing 0.02-0.04 g of MIL-100 (Fe) nanoparticles in 50 mL of deionized water, and obtaining the MOFs dispersed solution after a third stirring treatment; the third stirring treatment adopts a rotation speed of 200-250 rpm and a stirring time of 12-18 h.

[0021] Optionally, the preparation steps of the MIL-100(Fe) nanoparticles include:

[0022] (1) dissolving ferric chloride hexahydrate and 1,3,5-trimethylbenzene carboxylic acid in a molar ratio of 2:1-1:2 in 50-100 mL of N,N-dimethylformamide, and stirring until completely dissolved to obtain solution C; wherein the molar concentrations of the ferric chloride hexahydrate and the 1,3,5-trimethylbenzene carboxylic acid are both 1.0-3.0 mmol / L;

[0023] (2) pouring solution C into a stainless steel autoclave lined with polytetrafluoroethylene, heat treating at 120-180° C. for 12-14 h, washing, drying, and grinding to obtain MIL-100(Fe) nanoparticles;

[0024] The washing is carried out by using N,N-dimethylformamide and ethanol in sequence; the drying is carried out at a temperature of 60 to 80° C. and a drying time of 12 to 24 hours.

[0025] In a second aspect, the present invention provides a photoelectrocatalytic material electrode, which is prepared by the preparation method of the photoelectrocatalytic material electrode.

[0026] In the third aspect, the present invention provides an application of the photoelectrocatalytic material electrode in the degradation of tetracycline wastewater, wherein the photoelectrocatalytic material electrode is used as an anode, a platinum sheet electrode is used as a counter electrode, and a saturated calomel electrode is used as a reference electrode, and is placed in tetracycline wastewater containing an electrolyte to carry out a photoelectrocatalytic reaction, thereby completing the degradation treatment of the tetracycline wastewater.

[0027] Optionally, the photoelectrocatalytic reaction is carried out under light conditions, the voltage used in the photoelectrocatalytic reaction is 1.5-2V, and the reaction time is 1-3h; the electrolyte includes sodium sulfate; the pH value of the tetracycline wastewater is 4.5-5.0; the concentration of tetracycline in the tetracycline wastewater is 10-20mg / L, and the electrolyte concentration is 25-50mmol / L.

[0028] The application of the technical solution of the present invention has at least the following beneficial effects:

[0029] (1) The present invention provides a method for preparing a photoelectrocatalytic material electrode, which combines cellulose nanofiber hydrogel with titanium dioxide and MOFs to obtain a green, efficient and stable photoelectrocatalytic material, which can further promote the development and application of photoelectrocatalytic technology in tetracycline wastewater treatment and provide new guarantees for the qualified discharge and reuse of tetracycline wastewater. Specifically, the cellulose nanofiber hydrogel used in the present invention has a densely stacked and entangled nanofiber network structure, which can provide more catalytic active sites; at the same time, its good mechanical properties enable the catalyst MOFs to be firmly fixed in the three-dimensional network structure of the hydrogel, reducing the loss of the catalyst and ensuring the efficiency of continuous catalytic degradation. The self-assembly of MOFs inside the cellulose nanofiber hydrogel and at the contact interface can achieve chemical bonding inside and at the interface of the two to form an interwoven network structure and obtain a "double three-dimensional" structure. In addition, the highly entangled cellulose nanofiber hydrogel scaffold at the nanoscale can fully disperse MOFs and improve their ductility, providing a "self-supporting" effect for the structural stability of the photoelectrode under higher applied voltages.

[0030] (2) The dual three-dimensional structure photoelectrocatalytic material electrode prepared by the present invention uses cellulose nanofiber hydrogel doped with titania as the electrode substrate, and MIL-100 (Fe) nanoparticles are uniformly loaded on the electrode substrate, which solves the problems of easy loss of catalyst powder, difficulty in recovery and easy secondary pollution. The successful composite of titania and MIL-100 (Fe) improves the charge separation efficiency of titania, increases the separation efficiency of photogenerated carriers of the electrode, and realizes the efficient degradation of tetracycline under visible light conditions. In addition, the dual three-dimensional network structure formed by the composite of cellulose nanofiber hydrogel and MIL-100 (Fe) supports each other, effectively avoiding the problem of skeleton collapse of the material during the photoelectrocatalytic process, improving the stability of the photoelectrocatalytic material electrode, and making the electrode have a high promotion value and application prospect in the actual tetracycline wastewater treatment.

[0031] (3) The present invention uses a photoelectrocatalytic material electrode to degrade tetracycline wastewater, with a visible light responsive dual three-dimensional structure photoelectrocatalytic material electrode as an anode, a platinum sheet electrode as a counter electrode, and a saturated calomel electrode as a reference electrode, and is placed in tetracycline wastewater containing electrolytes for photoelectrocatalytic reaction, thereby achieving catalytic degradation of tetracycline in wastewater. Compared with the modified cellulose nanofiber hydrogel without MOFs loading, the degradation efficiency of the visible light responsive dual three-dimensional structure photoelectrocatalytic material electrode for treating tetracycline-containing wastewater is increased by 3.86 times; the synergy factor of the photoelectrocatalytic process is 6.66; after 4 cycles, the degradation ability of the visible light responsive dual three-dimensional structure photoelectrocatalytic material electrode for tetracycline has not decreased, showing the advantages of good light response performance, excellent catalytic effect, stable use performance, and eco-friendly environment, and has broad application prospects in the field of photoelectrocatalytic degradation of tetracycline wastewater.

[0032] In addition to the above-described purposes, features and advantages, the present invention has other purposes, features and advantages. The present invention will be further described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The drawings constituting a part of this application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0034] Figure 1a This is a scanning electron microscope image of the cellulose nanofiber hydrogel electrode CNF prepared in Comparative Example 1;

[0035] Figure 1b This is a scanning electron microscope image of the titania-doped cellulose nanofiber hydrogel electrode Ti4O7@CNF prepared in Comparative Example 2;

[0036] Figure 1cThis is a scanning electron microscope image of the cellulose nanofiber hydrogel electrode MIL-100(Fe)@CNF loaded with MIL-100(Fe) prepared in Comparative Example 3;

[0037] Figure 1d This is a scanning electron microscope image of the dual three-dimensional structure photoelectrocatalytic material electrode MIL-100(Fe) / Ti4O7@CNF prepared in Example 1;

[0038] Figure 2 X-ray diffraction patterns of the photoelectrodes prepared in Example 1 and Comparative Examples 1-3;

[0039] Figure 3a The UV-visible diffuse reflectance spectra of the photoelectrodes prepared in Example 1 and Comparative Examples 1-3 are shown;

[0040] Figure 3b The band gap energy diagram of each photoelectrode prepared in Example 1 and Comparative Examples 1-3;

[0041] Figure 4 The electrochemical impedance spectra of the photoelectrodes prepared in Example 1 and Comparative Examples 1-3 are shown.

[0042] Figure 5a The degradation effect diagram of tetracycline wastewater by the photoelectrodes prepared in Example 1 and Comparative Examples 1-3;

[0043] Figure 5b for Figure 5a The corresponding (pseudo) first-order kinetics curves;

[0044] Figure 6a The degradation effect diagram of tetracycline wastewater under different application conditions of Example 2 and Comparative Examples 4-5 is shown;

[0045] Figure 6b for Figure 6a Corresponding (pseudo) first-order kinetics plot;

[0046] Figure 7a The degradation effect diagram of tetracycline wastewater under different pH conditions is shown in Example 3 and Comparative Examples 6-10;

[0047] Figure 7b for Figure 7a Corresponding (pseudo) first-order kinetics plot;

[0048] Figure 8a The degradation effect diagram of tetracycline wastewater under different voltage conditions is shown in Example 4 and Comparative Examples 11-13;

[0049] Figure 8b for Figure 8a Corresponding (pseudo) first-order kinetics plot;

[0050] Figure 9a The figure is a graph showing the degradation effect of different photon fluxes on tetracycline wastewater in Examples 5-8;

[0051] Figure 9b for Figure 9a The corresponding (pseudo) first-order kinetics curves;

[0052] Fig.10a The degradation effect diagram of tetracycline wastewater by the photoelectrodes prepared in Example 1 and Comparative Example 14;

[0053] Fig.10b for Fig.10a The corresponding (pseudo) first-order kinetics curves;

[0054] Fig.11a The degradation effect diagram of tetracycline wastewater by the photoelectrodes prepared in Example 1 and Comparative Example 15;

[0055] Fig.11b for Fig.11a Corresponding (pseudo) first-order kinetics curves. DETAILED DESCRIPTION

[0056] The following will be combined with the accompanying drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.

[0057] Embodiment 1:

[0058] A method for preparing a photoelectrocatalytic material electrode, comprising:

[0059] Step S1, preparing titania-doped cellulose nanofiber hydrogel;

[0060] Step S2, after the titania-doped cellulose nanofiber hydrogel has been subjected to the first pretreatment, titanium bars subjected to the second pretreatment are respectively attached to the front and back sides of one end of the titania-doped cellulose nanofiber hydrogel to obtain a titania-doped cellulose nanofiber hydrogel electrode sheet;

[0061] Step S3, immersing the portion of the electrode sheet below the titanium strip into a MOFs dispersion solution, performing loading treatment under stirring, and obtaining a dual three-dimensional structure photoelectrocatalytic material electrode (abbreviated as photoelectrode, named MIL-100(Fe) / Ti4O7@CNF).

[0062] In step S1:

[0063] First, a hydrogel solution A is prepared. Specifically, 20 to 40 g (specifically 20 g) of cellulose nanofiber hydrogel, 0.3 to 0.6 g (specifically 0.3 g) of agar powder and 16 to 32 mL (specifically 16 mL) of deionized water are mixed, and then the mixture is subjected to a water bath treatment and a first continuous stirring treatment to obtain a hydrogel solution A;

[0064] Secondly, under the water bath treatment and the first stirring treatment, 0.25-0.35 g (specifically 0.3 g) of titanium dioxide powder is added to the hydrogel solution A and mixed;

[0065] Subsequently, a second stirring treatment is continued at room temperature (specifically 25° C.) until the solution is completely dissolved to obtain a solution B;

[0066] Finally, the solution B is poured into a culture dish, and an acidifier and a cross-linking agent are added thereto. After drying, the titanium dioxide-doped cellulose nanofiber hydrogel is obtained.

[0067] The temperature used in the water bath treatment is 85-90°C (specifically 90°C); the rotation speed used in the first stirring treatment is 400-500rpm (specifically 450rpm), and the stirring time is 5min; the rotation speed used in the second stirring treatment is 1000-1100rpm (specifically 1000rpm), and the stirring time is 2-3h (specifically 2h).

[0068] The acidulant is sulfuric acid; the concentration of the acidulant is 1 mol / L, and the volume is 3-4 mL (specifically 4 mL); the crosslinking agent is N,N′-methylenebisacrylamide solution; the mass concentration of the N,N′-methylenebisacrylamide solution is 4wt%, and the volume is 3-4 mL (specifically 4 mL); the drying temperature used in the drying treatment is 60°C, and the drying time is 45 min.

[0069] The first pretreatment includes sequentially washing the titanium suboxide-doped cellulose nanofiber hydrogel with deionized water and cutting it into square sheets with a side length of 3 cm; the second pretreatment includes first ultrasonically removing impurities from the surface of the titanium sheet and then cutting it into titanium strips with a length of 3 cm and a width of 0.5 cm; the surface ultrasonic impurity removal is to ultrasonically treat the titanium sheet with acetone, ethanol and deionized water for 15 minutes each in sequence to remove impurities on the surface of the titanium sheet; the binder is an ethanol solution of polyvinyl pyrrolidone, wherein the mass fraction of polyvinyl pyrrolidone in the ethanol solution is 5wt%.

[0070] The MOFs dispersed solution comprises dispersing 0.02 to 0.04 g (specifically 0.03 g) of MIL-100 (Fe) nanoparticles in 50 mL of deionized water, and obtaining the MOFs dispersed solution after a third stirring treatment; the rotation speed used in the third stirring treatment is 200 to 250 rpm (specifically 220 rpm), and the stirring time is 12 to 18 h (specifically 18 h).

[0071] The preparation steps of the MIL-100 (Fe) nanoparticles include:

[0072] (1) dissolving ferric chloride hexahydrate and 1,3,5-trimethylbenzene in a molar ratio of 1:1 in 50 mL of N,N-dimethylformamide, and stirring until completely dissolved to obtain solution C; wherein the molar concentrations of the ferric chloride hexahydrate and the 1,3,5-trimethylbenzene are both 2.5 mmol / L;

[0073] (2) pouring solution C into a stainless steel autoclave lined with polytetrafluoroethylene, heat treating at 150° C. for 12 to 14 h (specifically 12 h), washing, drying, and grinding to obtain MIL-100 (Fe) nanoparticles;

[0074] The washing is carried out in sequence by washing with N,N-dimethylformamide for 2 times and washing with ethanol for 1 time; the drying temperature is 60-80° C. (specifically 60° C.), and the drying time is 12-24 hours (specifically 18 hours).

[0075] Comparative Example 1:

[0076] Different from Example 1, only cellulose nanofiber hydrogel electrode (named as CNF) was prepared, that is, the use of titania powder and MOFs dispersion solution was eliminated.

[0077] Comparative Example 2:

[0078] Different from Example 1, a titania-doped cellulose nanofiber hydrogel electrode (named Ti4O7@CNF) was prepared, that is, the use of MOFs dispersed solution was eliminated.

[0079] Comparative Example 3:

[0080] Different from Example 1, a cellulose nanofiber hydrogel electrode loaded with MIL-100(Fe) (named as MIL-100(Fe)@CNF) was prepared, that is, the use of titania powder was eliminated.

[0081] The photoelectrodes prepared in Example 1 and Comparative Examples 1-3 were tested by scanning electron microscope. The test results are as follows:

[0082] Figure 1aThis is a scanning electron microscope image of the cellulose nanofiber hydrogel electrode CNF prepared in Comparative Example 1. It can be seen that the CNF has a cross-linked structure and a smooth surface with wavy wrinkles.

[0083] Figure 1b This is a scanning electron microscope image of the titania-doped cellulose nanofiber hydrogel electrode Ti4O7@CNF prepared in Comparative Example 2. It can be seen that in Ti4O7@CNF, CNF wraps and fixes the titania, presenting a stacked wrinkled structure. Such structural features are conducive to the loading of MIL-100(Fe) in the solution on Ti4O7@CNF, thereby increasing the loading amount of MIL-100(Fe) nanoparticles.

[0084] Figure 1c This is a scanning electron microscope image of the cellulose nanofiber hydrogel electrode MIL-100(Fe)@CNF loaded with MIL-100(Fe) prepared in comparative example 3. It can be seen that the surface of MIL-100(Fe) introduced with pure CNF is rough and presents an irregular octahedral structure.

[0085] Figure 1d This is a scanning electron microscope image of the dual three-dimensional structure photoelectrocatalytic material electrode MIL-100(Fe) / Ti4O7@CNF prepared in Example 1. It can be seen that the MIL-100(Fe) nanoparticles on the surface of MIL-100(Fe) / Ti4O7@CNF can be clearly observed as complete octahedrons.

[0086] Depend on Figure 1a-1d From the analysis, it can be concluded that the composite of MIL-100(Fe) and Ti4O7@CNF is beneficial to the formation of regular morphology of MIL-100(Fe), thereby improving its photoelectrocatalytic performance.

[0087] The photoelectrodes prepared in Example 1 and Comparative Examples 1-3 were subjected to X-ray diffraction tests. The test results are as follows:

[0088] Depend on Figure 2 It was observed that the X-ray diffraction pattern of the MIL-100(Fe) / Ti4O7@CNF composite material showed characteristic diffraction peaks near 14.1° and 20.2°, which matched those of MIL-100(Fe), proving the successful synthesis and loading of MIL-100(Fe). However, no diffraction peaks at 11.3°, 18.4°, and 24.2° were observed in the X-ray diffraction pattern. This may be due to some minor changes in the crystal structure of MIL-100(Fe) after the composite of MIL-100(Fe) and Ti4O7@CNF, resulting in the shift of the diffraction peaks. In addition, Figure 2It was also observed that Ti4O7@CNF and MIL-100(Fe) / Ti4O7@CNF had diffraction peaks at 2θ of 20.74°, 26.35°, 29.57°, 31.82°, 34.08°, 35.60°, 53.31° and 55.05°, respectively. Comparing with the standard X-ray diffraction spectrum of titanium dioxide (JCPDS no.77-1392), it was found that these diffraction peaks were highly matched with the characteristic diffraction peaks of titanium dioxide, proving that titanium dioxide was successfully composited in the photoelectrode.

[0089] The photoelectrodes prepared in Example 1 and Comparative Examples 1-3 were tested for UV-visible diffuse reflection light. The test results are as follows:

[0090] Depend on Figure 3a It can be concluded that the absorption edges of the photoelectrodes prepared in Example 1 and Comparative Examples 1-3 are all within the range of ultraviolet light, indicating that the electrodes of the four materials can absorb ultraviolet light very well. Among them, CNF and MIL-100(Fe)@CNF both have obvious steep absorption edges, and the absorption edge wavelengths are 370nm and 421nm, respectively. It is worth noting that due to the smaller bandgap width of titanium oxide, the ability of Ti4O7@CNF and MIL-100(Fe) / Ti4O7@CNF to absorb light is much better than that of MIL-100(Fe)@CNF and CNF; among them, Ti4O7@CNF has relatively strong light absorption capacity, and its absorbable light range extends all the way to visible light, especially in the range of 300nm to 800nm, with significantly enhanced light absorption.

[0091] According to the Kubellka-Munk equation (i.e., equation 1), the absorption data of different wavelengths obtained under the ultraviolet visible diffuse reflection light test of each photoelectrode material prepared in Example 1 and Comparative Examples 1-3 are converted into a Tauc diagram to evaluate the band gap energy (E g ).like Figure 3b The E of samples CNF, Ti4O7@CNF, MIL-100(Fe)@CNF and MIL-100(Fe) / Ti4O7@CNF g The values ​​are 4.03eV, 3.75eV, 4.31eV and 3.88eV respectively; among them, the E g The value is the smallest, indicating that Ti4O7@CNF has relatively excellent light absorption ability, which is consistent with the conclusion drawn from the UV-visible diffuse reflectance spectrum. Although the light absorption ability of the composite MIL-100(Fe) / Ti4O7@CNF is slightly weaker than that of Ti4O7@CNF, compared with MIL-100(Fe)@CNF, the range of light absorption is greatly enhanced, and it still has relatively excellent light response performance.

[0092] (αhν) 2=A(hν-E g )(Equation 1);

[0093] In equation 1, α represents the absorption coefficient; hν represents the incident photon energy; A represents a constant that is related to the material properties; E g represents the band gap energy.

[0094] The photoelectrodes prepared in Example 1 and Comparative Examples 1-3 were subjected to electrochemical impedance tests. The test results are as follows:

[0095] Depend on Figure 4 It can be seen that the curve radius of MIL-100(Fe) / Ti4O7@CNF is the smallest. This phenomenon indicates that the successful introduction of MIL-100(Fe) significantly enhances the photogenerated carrier transfer efficiency of Ti4O7@CNF, making MIL-100(Fe) / Ti4O7@CNF have the best photoelectric performance.

[0096] Embodiment 2:

[0097] The photoelectrode (MIL-100(Fe) / Ti4O7@CNF) prepared in Example 1 was used as an anode, a platinum electrode was used as a counter electrode, and a saturated calomel electrode was used as a reference electrode. It was placed in 100 mL of tetracycline wastewater containing sodium sulfate (the concentration of sodium sulfate in the wastewater was 50 mmol / L, the concentration of tetracycline was 20 mg / L, and pH = 4.75). A photoelectrocatalytic reaction was carried out for 120 minutes under the conditions of visible light source and a constant voltage of 2 V to complete the degradation of tetracycline; wherein the photoelectrode was 10 cm away from the light source.

[0098] The photoelectrodes prepared in Comparative Examples 1-3 were used as anodes, and the tetracycline wastewater degradation experiments were carried out according to the same operating conditions as in Example 2. During the 120-min photoelectrocatalytic reaction, 1 mL of sample was taken every 30 minutes (i.e., when the catalysis was carried out for 0 minutes, 30 minutes, 60 minutes, 90 minutes and 120 minutes) and passed through a 0.45 μm filter. The change in peak area at different degradation times was measured by high performance liquid chromatography to determine the change in tetracycline concentration during the photoelectrocatalytic process, thereby obtaining the degradation effect of each photoelectrode on tetracycline. The degradation effect is shown in FIG. Figure 5a-Figure 5b shown.

[0099] Depend on Figure 5a It can be seen that the T i4The degradation capacity of O7@CNF electrode for tetracycline is very limited, only 24.14%, which is due to the high transfer resistance of titanium oxide interface and low electrocatalytic activity. MIL-100(Fe)@CNF can degrade 66.43% of tetracycline within 120 minutes, and the successfully composited MIL-100(Fe) / Ti4O7@CNF electrode can degrade 93.22% of tetracycline within 120 minutes, which is 3.86 times the degradation efficiency of Ti4O7@CNF.

[0100] Depend on Figure 5b It can be seen that the reaction rate of MIL-100(Fe) / Ti4O7@CNF is greatly increased compared with other photoelectrodes, from 0.00178 min for CNF electrode to -1 Increased to 0.02246min for MIL-100(Fe) / Ti4O7@CNF electrode -1 , which indicates that the photoelectrocatalytic performance of MIL-100(Fe) / Ti4O7@CNF is significantly improved after the introduction of MIL-100(Fe) into Ti4O7@CNF.

[0101] Comparative Example 4:

[0102] The difference from Example 2 is that the applied condition is only a visible light source.

[0103] Comparative Example 5:

[0104] The difference from Example 2 is that the applied condition is only a constant voltage of 2V.

[0105] During the 120-min photoelectrocatalytic reaction in Example 2 and Comparative Examples 4-5, 1 mL of sample was taken every 30 min (i.e., when the catalysis was performed for 0 min, 30 min, 60 min, 90 min and 120 min) and passed through a 0.45 μm filter. The change in peak area at different degradation times was measured by high performance liquid chromatography to determine the change in tetracycline concentration during the photoelectrocatalytic process, thereby obtaining the degradation effect of each photoelectrode on tetracycline under different application conditions. The degradation effect is shown in FIG. Figure 6a-6b shown.

[0106] Depend on Figure 6a It is known that under the conditions of applying visible light source alone (i.e. photocatalysis) and applying constant voltage of 2V alone (i.e. electrocatalysis), after 120 minutes of reaction, the degradation rate of tetracycline by MIL-100(Fe) / Ti4O7@CNF electrode is low, 16.20% and 23.69% respectively. Under the conditions of applying visible light source and 2V constant voltage at the same time (i.e. photoelectrocatalysis), the degradation rate can be as high as 93.22%, which is significantly better than photocatalysis and electrocatalysis; this proves that there is a significant synergistic effect of light and electricity in the photoelectrocatalytic process.

[0107] according to Figure 6b The first-order kinetic constant (k) of the photoelectrocatalytic process was calculated using Equation 2 to give a synergistic factor (SF) of 6.66.

[0108]

[0109] Where k in Equation 2 PEC , k PC and k EC represent the first-order kinetic constants of tetracycline degradation in the photoelectrocatalytic, photocatalytic and electrocatalytic processes, respectively.

[0110] Embodiment 3:

[0111] The difference from Example 2 is that pH=5.

[0112] Comparative Example 6:

[0113] The difference from Example 2 is that pH=1.

[0114] Comparative Example 7:

[0115] The difference from Example 2 is that pH=3.

[0116] Comparative Example 8:

[0117] The difference from Example 2 is that the pH is 7.

[0118] Comparative Example 9:

[0119] The difference from Example 2 is that pH=9.

[0120] Comparative Example 10:

[0121] The difference from Example 2 is that pH=11.

[0122] During the 120-min photoelectrocatalytic reaction in Example 3 and Comparative Examples 6-10, 1 mL of sample was taken every 30 min (i.e., when the catalysis was performed for 0 min, 30 min, 60 min, 90 min and 120 min) and passed through a 0.45 μm filter. The change in peak area at different degradation times was measured by high performance liquid chromatography to determine the change in tetracycline concentration during the photoelectrocatalytic process, thereby obtaining the degradation effect of each photoelectrode on tetracycline under different pH conditions. The degradation effect is shown in FIG. Figure 7a-Figure 7b shown.

[0123] Depend on Figure 7a and 7bIt is known that in the strong acid environment of pH = 1 and 3, the degradation rate of tetracycline by MIL-100(Fe) / Ti4O7@CNF is about 55%, and the first-order kinetic constants k are 0.00657 and 0.00647, respectively, which are both low. This is because the catalytic sites on the catalyst surface are limited, and H + At higher concentrations, H + It occupies the active sites on the surface of the photoelectrode, hindering the adsorption and degradation of tetracycline. In addition, it may also be due to excessive H + Reacting with ·OH, the amount of ·OH decreases and the degradation rate decreases; when pH = 5, close to the initial pH value of 4.75, the degradation rate of tetracycline is 95.24%, which indicates that in a weakly acidic environment, MIL-100 (Fe) / Ti4O7 @ CNF can achieve efficient degradation of tetracycline. Afterwards, as the pH of the solution increases, the degradation efficiency gradually decreases, but when the pH increases to 11, the degradation rate of tetracycline by MIL-100 (Fe) / Ti4O7 @ CNF reaches the maximum value, with a degradation rate of up to 96.03% within 60 minutes, and 100% degradation of tetracycline is achieved within 120 minutes. The first-order kinetic constant k of the reaction is as high as 0.04243. Analysis of this phenomenon may have the following reasons: 1) The nature of the target pollutant, tetracycline is unstable in a strong alkaline aqueous solution, will be partially hydrolyzed, and will also undergo a reversible isomerization reaction to generate an isomer with a lactone structure; 2) There are a large number of OH in the solution - , more active substances (such as ·OH, ·O 2- ), the active substance reacts with tetracycline to accelerate the degradation rate.

[0124] Embodiment 4:

[0125] The difference from Example 2 is that the voltage is adjusted to 1.5V.

[0126] Comparative Example 11:

[0127] The difference from Example 2 is that the voltage is adjusted to 2.5V.

[0128] Comparative Example 12:

[0129] The difference from Example 2 is that the voltage is adjusted to 1V.

[0130] Comparative Example 13:

[0131] The difference from Example 2 is that the voltage is adjusted to 0.5V.

[0132] During the 120-min photoelectrocatalytic reaction in Example 4 and Comparative Examples 11-13, 1 mL of sample was taken every 30 min (i.e., when the catalysis was performed for 0 min, 30 min, 60 min, 90 min and 120 min) and passed through a 0.45 μm filter. The change in peak area at different degradation times was measured by high performance liquid chromatography to determine the change in tetracycline concentration during the photoelectrocatalytic process, thereby obtaining the degradation effect of each photoelectrode on tetracycline under different voltage conditions. The degradation effect is shown in FIG. Figure 8a-8b shown.

[0133] Depend on Figure 8a It is known that under the conditions of voltage of 0.5V, 1.0V, 1.5V, 2V and 2.5V, the degradation rate of tetracycline by MIL-100(Fe) / Ti4O7@CNF is 9.69%, 16.34%, 76.02%, 93.22% and 96.89% respectively; Figure 8b It is known that the first-order kinetic constant (k) also changes from 0.00087min at 0.5V to -1 0.03002min when increasing to 2.5V -1 , that is, as the voltage continues to increase, the degradation rate of tetracycline gradually increases. This may be because the increase in voltage promotes the transfer of charge in the reaction system, improves the reaction activity and catalytic efficiency. However, when the voltage increases to 2.5V, bubbles and holes appear on the surface of the photoelectrode. This is because the side reactions in the system (such as hydrogen evolution and oxygen evolution reactions) are significantly enhanced under higher applied voltages. In order to ensure the life of the photoelectrode and stable degradation efficiency, a voltage of 2V is the most suitable applied voltage.

[0134] Embodiment 5:

[0135] The difference from Example 2 is that the distance between the photoelectrode and the light source is 6 cm.

[0136] Embodiment 6:

[0137] Different from Example 2, the distance between the photoelectrode and the light source is 8 cm.

[0138] Embodiment 7:

[0139] Different from Example 2, the distance between the photoelectrode and the light source is 12 cm.

[0140] Embodiment 8:

[0141] Different from Example 2, the distance between the photoelectrode and the light source is 14 cm.

[0142] In Examples 2 and 5-8, the photon flux was varied by changing the distance between the light source and the photoelectrode.

[0143] During the 120-min photoelectrocatalytic reaction in Examples 2 and 5-8, 1 mL of sample was taken every 30 min (i.e., when the catalysis was performed for 0 min, 30 min, 60 min, 90 min and 120 min) and passed through a 0.45 μm filter. The change in peak area at different degradation times was measured by high performance liquid chromatography to determine the change in tetracycline concentration during the photoelectrocatalytic process, thereby obtaining the degradation effect of each photoelectrode on tetracycline under different photon flux conditions. The degradation effect is shown in FIG. Figure 9a-9b shown.

[0144] Figure 9a The effect of different photon fluxes on the tetracycline degradation efficiency of MIL-100(Fe) / Ti4O7@CNF electrode is shown. It can be seen that the tetracycline degradation efficiency gradually increases with the decrease of the distance between the photoelectrode and the light source; when the distance is reduced to 6cm, MIL-100(Fe) / Ti4O7@CNF can degrade up to 98.11% of tetracycline; when the distance increases to 14cm, the degradation efficiency of tetracycline is 91.48%.

[0145] Figure 9b Figure 3 is the (pseudo) first-order kinetic curve of tetracycline degradation under different photon flux conditions. The first-order kinetic constant (k) obtained by analysis and fitting shows that the k value of high photon flux is 1.69 times that of low photon flux. This is because with the increase of photon flux, the number of electrons generated by photon excitation increases, which increases the degradation rate of tetracycline.

[0146] Comparative Example 14:

[0147] The difference from Example 1 is that the amount of titanium dioxide powder used is 0.15 g.

[0148] Comparative Example 15:

[0149] The difference from Example 1 is that the amount of MIL-100 (Fe) nanoparticles used is 0.06 g.

[0150] The photoelectrodes prepared in Example 1 and Comparative Example 14 were used as anodes, and the tetracycline wastewater degradation experiments were carried out according to the same operating conditions as in Example 2. During the 120-min photoelectrocatalytic reaction, 1 mL of sample was taken every 30 minutes (i.e., when the catalysis was carried out for 0 minutes, 30 minutes, 60 minutes, 90 minutes and 120 minutes) and passed through a 0.45 μm filter. The change in peak area at different degradation times was measured by high performance liquid chromatography to determine the change in tetracycline concentration during the photoelectrocatalytic process, thereby obtaining the degradation effect of each photoelectrode on tetracycline. The degradation effect is shown in FIG. Figure 10a-Figure 10b shown.

[0151] Depend on Fig.10a and Fig.10bIt can be seen that when preparing MIL-100(Fe) / Ti4O7@CNF photoelectrode, when the amount of titania powder is 0.15g, the degradation rate of tetracycline by the corresponding photoelectrode within 120min is only 44.22%, and the first-order kinetic constant is 0.00405; when the amount of titania powder is increased to 0.3g, the degradation rate of tetracycline by the corresponding photoelectrode within 120min reaches 93.22%, and the first-order kinetic constant also increases to 0.02246. Compared with the addition of 0.15g titania powder, the degradation efficiency increases by 2.1 times and the reaction rate increases by 5.5 times.

[0152] The photoelectrodes prepared in Example 1 and Comparative Example 15 were used as anodes, and the tetracycline wastewater degradation experiments were carried out according to the same operating conditions as in Example 2. During the 120-min photoelectrocatalytic reaction, 1 mL of sample was taken every 30 minutes (i.e., when the catalysis was carried out for 0 minutes, 30 minutes, 60 minutes, 90 minutes and 120 minutes) and passed through a 0.45 μm filter. The change in peak area at different degradation times was measured by high performance liquid chromatography to determine the change in tetracycline concentration during the photoelectrocatalytic process, thereby obtaining the degradation effect of each photoelectrode on tetracycline. The degradation effect is shown in FIG. Figure 11a-Figure 11b shown.

[0153] Depend on Fig.11a and Fig.11b It can be seen that when preparing MIL-100(Fe) / Ti4O7@CNF photoelectrode, when the dosage of MIL-100(Fe) nanoparticles is 0.03g and 0.06g respectively, the degradation rates of tetracycline by the corresponding photoelectrodes within 120min are 93.22% and 92.66% respectively, and the first-order kinetic constants are 0.02246 and 0.02324; since the degradation efficiencies obtained by adding 0.03g and 0.06g of MIL-100(Fe) nanoparticles are both above 90% and the difference is not large, in order to save production costs, the preferred dosage of MIL-100(Fe) nanoparticles is 0.03g.

[0154] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a photoelectrocatalytic material electrode, characterized in that: include: Step S1, preparing titania-doped cellulose nanofiber hydrogel; Step S2, after the titania-doped cellulose nanofiber hydrogel has been subjected to the first pretreatment, titanium bars subjected to the second pretreatment are respectively attached to the front and back sides of one end of the titania-doped cellulose nanofiber hydrogel to obtain a titania-doped cellulose nanofiber hydrogel electrode sheet; Step S3, immersing the portion of the electrode sheet below the titanium strip into a MOFs dispersion solution, and performing a loading treatment under stirring to obtain a dual three-dimensional structure photoelectrocatalytic material electrode.

2. The method for preparing a photoelectrocatalytic material electrode according to claim 1, characterized in that: In step S1: First, a hydrogel solution A is prepared. Specifically, 20 to 40 g of cellulose nanofiber hydrogel, 0.3 to 0.6 g of agar powder and 16 to 32 mL of deionized water are mixed, and then the mixture is subjected to a water bath treatment and a first continuous stirring treatment to obtain a hydrogel solution A. Secondly, under the water bath treatment and the first stirring treatment, 0.25-0.35 g of titanium dioxide powder is added to the hydrogel solution A and mixed; Then, the mixture was stirred for a second time at room temperature until it was completely dissolved, thereby obtaining solution B; Finally, the solution B is poured into a culture dish, and an acidifier and a cross-linking agent are added thereto. After drying, the titanium dioxide-doped cellulose nanofiber hydrogel is obtained.

3. The method for preparing a photoelectrocatalytic material electrode according to claim 2, characterized in that: The temperature used in the water bath treatment is 85-90°C; the rotation speed used in the first stirring treatment is 400-500rpm, and the stirring time is 3-5min; the rotation speed used in the second stirring treatment is 1000-1100rpm, and the stirring time is 2-3h.

4. The method for preparing a photoelectrocatalytic material electrode according to claim 2, characterized in that: The acidulant comprises sulfuric acid; the concentration of the acidulant is 0.5-2.0 mol / L, and the volume is 3-4 mL; the crosslinking agent comprises N,N′-methylenebisacrylamide solution; the mass concentration of the N,N′-methylenebisacrylamide solution is 3.5-4.5 wt %, and the volume is 3-4 mL; the drying temperature adopted in the drying treatment is 50-80° C., and the drying time is 45-60 min.

5. The method for preparing a photoelectrocatalytic material electrode according to claim 1, characterized in that: The first pretreatment includes deionized water cleaning and cutting of the titania-doped cellulose nanofiber hydrogel in sequence; the second pretreatment includes ultrasonically removing impurities from the surface of the titanium sheet and then cutting it into titanium strips; the adhesive includes an ethanol solution of polyvinyl pyrrolidone.

6. The method for preparing a photoelectrocatalytic material electrode according to claim 1, characterized in that: The MOFs dispersion solution comprises dispersing 0.02-0.04g of MIL-100 (Fe) nanoparticles in 50mL of deionized water, and obtaining the MOFs dispersion solution after a third stirring treatment; the third stirring treatment adopts a rotation speed of 200-250rpm and a stirring time of 12-18h.

7. The method for preparing a photoelectrocatalytic material electrode according to claim 6, characterized in that: The preparation steps of the MIL-100 (Fe) nanoparticles include: (1) dissolving ferric chloride hexahydrate and 1,3,5-trimethylbenzene carboxylic acid in a molar ratio of 2:1-1:2 in 50-100 mL of N,N-dimethylformamide, and stirring until completely dissolved to obtain solution C; wherein the molar concentrations of the ferric chloride hexahydrate and the 1,3,5-trimethylbenzene carboxylic acid are both 1.0-3.0 mmol / L; (2) pouring solution C into a stainless steel autoclave lined with polytetrafluoroethylene, heat treating at 120-180° C. for 12-14 h, washing, drying, and grinding to obtain MIL-100(Fe) nanoparticles; The washing is carried out by using N,N-dimethylformamide and ethanol in sequence; the drying is carried out at a temperature of 60 to 80° C. and a drying time of 12 to 24 hours.

8. A photoelectrocatalytic material electrode, characterized in that: The photoelectrocatalytic material electrode is prepared by the method for preparing the photoelectrocatalytic material electrode as described in any one of claims 1 to 7.

9. An application of the photoelectrocatalytic material electrode as claimed in claim 8 in degrading tetracycline wastewater, characterized in that: The photoelectrocatalytic material electrode is used as an anode, a platinum sheet electrode is used as a counter electrode, and a saturated calomel electrode is used as a reference electrode. The electrodes are placed in tetracycline wastewater containing electrolytes to carry out a photoelectrocatalytic reaction, thereby completing the degradation treatment of the tetracycline wastewater.

10. The use according to claim 9, characterized in that: The photoelectrocatalytic reaction is carried out under light conditions, the voltage used in the photoelectrocatalytic reaction is 1.5-2V, and the reaction time is 1-3h; the electrolyte includes sodium sulfate; the pH value of the tetracycline wastewater is 4.5-5.0; the concentration of tetracycline in the tetracycline wastewater is 10-20mg / L, and the electrolyte concentration is 25-50mmol / L.

Citation Information

Patent Citations

  • Method of treating organic wastewater based on Fenton-like reaction of iron-based organic-framework material

    CN104310565A

  • Preparation and application of composite hydrogel capable of adsorbing and catalytically degrading antibiotics

    CN106423103A

  • Method for in-situ preparation of titanium dioxide / cellulose nano-composite microspheres

    CN114870905A

  • Graphite-phase carbon nitride / nanocellulose composite hydrogel as well as preparation method and application thereof

    CN115772275A

  • MOF / cellulose hydrogel, and preparation method therefor and use thereof

    WO2024244060A1

Cited By

  • Photoelectric cathode catalyst and electrode preparation method and application thereof

    CN121588839A

  • Photocathode catalyst and electrode preparation method and application thereof

    CN121588839B